2011
DOI: 10.3390/v3010012
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Population Dynamics in Mutualistic versus Pathogenic Viruses

Abstract: Although generally regarded as pathogens, viruses can also be mutualists. A number of examples of extreme mutualism (i.e., symbiogenesis) have been well studied. Other examples of mutualism are less common, but this is likely because viruses have rarely been thought of as having any beneficial effects on their hosts. The effect of mutualism on the population dynamics of viruses is a topic that has not been addressed experimentally. However, the potential for understanding mutualism and how a virus might become… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Studies of plant RNA viruses generally report small effective population sizes during transmission, whereas studies with one plant DNA virus reported a large population of virions during spread in single plant (21)(22)(23). The transmission of HIV between T cells involves transmission of a large number of virions across a virological synapse (2,24).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of plant RNA viruses generally report small effective population sizes during transmission, whereas studies with one plant DNA virus reported a large population of virions during spread in single plant (21)(22)(23). The transmission of HIV between T cells involves transmission of a large number of virions across a virological synapse (2,24).…”
Section: Discussionmentioning
confidence: 99%
“…However, an additional hypothesis could be postulated specifically for Chagas' heart disease. In theory, co-infection could modulate the complex interactions between parasite and host, and in addition, any infectious agent by itself might contribute to myocardial dysfunction [39][40][41]. Considering our findings, we would like to speculate that the increase in non T. cruzi microorganisms in the myocardial tissue could lead to an imbalance triggering worsening or full development of chagasic DCM.…”
Section: Co-infections and Chagas' Heart Diseasementioning
confidence: 75%
“…PDVs are an endogenous and integral part of endoparasitoid genome (Belle et al 2002) and are produced in the ovarian calyx of the wasp (Wyler and Lanzrein 2003). PDVs can deliver non-viral wasp genes into hosts to perform immune suppressive functions (Webb 1998;Roossinck 2011;Drezen et al 2014). PDVs became incorporated into certain groups of braconid and ichneumonid genomes in two independent events (Webb 1998), with braconid PDVs or bracoviruses originating~74 mya (Whitfield 2002).…”
Section: Viruses and Virus-like Particlesmentioning
confidence: 99%